Economic Growth Theories, And the Managing of Oil Curse; The Effect of Corruption - Masaud, Khair Ahmed; Eshawish, Aymen Alajly; Ertimi, Basem (Archives of Business Research, 2020)
The paper discusses that Corruption, resources, private investment and economic growth are related. The inference is that the potential benefits of rising corruption in deeply authoritarian nations are practically greater than any other government intervention. Corruption awareness is essential in policy decisions that accelerate the policy platform. Emerging economies, notably the Middle East and North African countries with ample resources, can make a major contribution. further, the impact of corruption on the accumulation of human capital across two channels. It occurs on the first channel. It has the impact of corruption in public education spending and the second path. Corruption in spending on physical capital and investment. The paper argues that the pace of the reform initiatives is crucial and that the success of the policies is affected by corruption and affirms the existence effect in human resources and corruption.